2012
DOI: 10.1007/s00226-012-0499-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining moisture-dependent elastic characteristics of beech wood by means of ultrasonic waves

Abstract: The present study investigates the influence of moisture content on the elastic characteristics of beech wood (Fagus sylvatica L.) by means of ultrasonic waves. A set of elastic engineering parameters (i.e. three Young's moduli, three shear moduli and six Poisson's ratios) is determined at four specific moisture contents. The results reveal the significant influence of the moisture content on the elastic behaviour of beech wood. With the exception of some Poisson's ratios, the engineering parameters decrease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 21 publications
8
30
1
4
Order By: Relevance
“…Por otra parte, Kránitz et al (2014) emplearon ultrasonido para la determinación del módulo de elasticidad en madera de P. abies con densidad de 465 kg·m -3 y 12 % de humedad, y obtuvieron G LR = 926 MPa, G LT = 863 MPa y G RT = 107 MPa. moduli of rigidity for the longitudinal-tangential plane determined by the authors: Naruse (2003), Keunecke et al (2007), Yoshihara (2012b), Ozyhar et al (2013), Kránitz et al (2014), Nadir et al (2014) and Sotomayor (2015), for woods with densities and humidity contents similar to the ones determined in this study. Figure 3 presents a graphic comparison between the G LT determined in these studies.…”
Section: ⎞ ⎠supporting
confidence: 79%
See 3 more Smart Citations
“…Por otra parte, Kránitz et al (2014) emplearon ultrasonido para la determinación del módulo de elasticidad en madera de P. abies con densidad de 465 kg·m -3 y 12 % de humedad, y obtuvieron G LR = 926 MPa, G LT = 863 MPa y G RT = 107 MPa. moduli of rigidity for the longitudinal-tangential plane determined by the authors: Naruse (2003), Keunecke et al (2007), Yoshihara (2012b), Ozyhar et al (2013), Kránitz et al (2014), Nadir et al (2014) and Sotomayor (2015), for woods with densities and humidity contents similar to the ones determined in this study. Figure 3 presents a graphic comparison between the G LT determined in these studies.…”
Section: ⎞ ⎠supporting
confidence: 79%
“…La frecuencia natural es un predictor del módulo de rigidez dinámico con una correlación de G LT = 3.41ρ -7,288 y R 2 = 0.81. Los valores del G LT de las siete especies mexicanas son similares a los módulos de rigidez para el plano longitudinal-tangencial determinados por los autores Naruse (2003), Keunecke et al (2007), Yoshihara (2012b), Ozyhar et al (2013), Kránitz et al (2014), Nadir et al (2014) y Sotomayor (2015, para maderas con densidades y contenidos de humedad similares a los determinados en el presente estudio. La Figura 3 presenta una comparación gráfica entre los G LT determinados en dichos estudios.…”
Section: ⎞ ⎠unclassified
See 2 more Smart Citations
“…The reason for this is because the rest of the elastic properties of the body affect wave propagation along one direction. Ozyhar et al (2013) concluded that obtaining the stiffness matrix when taking into account only the terms along the main diagonal of the matrix led to an over-estimation of the longitudinal and transversal elastic moduli.…”
Section: Fig 2 Ultrasound Test Devicementioning
confidence: 99%